Modular manufacturing processes: Status, challenges, and opportunities. Issue 10 (5th August 2017) - Baldea, Michael; Edgar, Thomas F.; Stanley, Bill L.; Kiss, Anton A.
Abstract : Chemical companies are constantly seeking new, high‐margin growth opportunities, the majority of which lie in high‐grade, specialty chemicals, rather than in the bulk sector. To realize these opportunities, manufacturers are increasingly considering decentralized, flexible production facilities: large‐scale production units are uneconomical for innovative products with a short lifespan and volatile markets. Small modular plants have low financial risks, are flexible and can respond rapidly to changes in demand. Logistics costs can be also reduced by moving production closer to customers and/or sources of raw materials. Moreover, stricter safety regulations can in many cases be more easily met using smaller distributed facilities. Modularization of chemical production can thus have potentially significant economic and safety benefits. In this article, several drivers for modular production are reviewed, and modular production architectures are evaluated based on a new metric, the value density of feedstock resources and markets for the products of a process. The links between modularization and process intensification are also discussed. Several industrial examples are provided and used to highlight challenges and future directions for this area. © 2017 American Institute of Chemical Engineers AIChE J, 63: 4262–4272, 2017